KARATERISTIK KESALAHAN SISWA SMP KELAS VIII DALAM MENYELESAIKAN SOAL PADA MATERI BANGUN RUANG SISI DATAR - Maria Tania Sesa; Devi Nurul Yuspriyati (IKIP Siliwangi, 2022)
The purpose of this study was will explain students' mistake when working on math problem on the lesson of flat-sided geometry material at SMP Negeri 8 Cimahi Class VIII, namely 27 people. Used qualitative research with descriptive method. How to collect data, namely test instruments and interview with seven description question. The results of the student's response test for question number five were 29.63%, for question number seven it was 37.04%, and for question number three it was 40.74% still very low. Research conducted by students is difficult when working on these question. Explanation of data and assessment of students made part type of errors, is: (1) students' difficulties in understanding concept; (2) difficulty understanding question or not being careful when understanding question so that students' response are incomplete; (3) difficulty in understanding mathematics theory or the prerequisites of the Pythagorean theorem; (4) lack of accuracy when working on the calculation phase. This proves that class VIII students are very low when working on the problem of building a flat side room.